CD4+TGFβ+ cells infiltrated the bursa of Fabricius following IBDV infection, and correlated with a delayed viral clearance, but did not correlate with disease severity, or immunosuppression - Nazki, Salik; Reddy, Vishwanatha R. A. P.; Kamble, Nitin; Sadeyen, Jean-Remy; Iqbal, Munir; Behboudi, Shahriar; Shelton, Holly; Broadbent, Andrew J. (Frontiers in Immunology, 2023)
Introduction Infectious Bursal Disease Virus (IBDV) causes immunosuppression in chickens. While B-cell destruction is the main cause of humoral immunosuppression, bursal T cells from IBDV-infected birds have been reported to inhibit the mitogenic response of splenocytes, indicating that some T cell subsets in the infected bursa have immunomodulatory activities. CD4+CD25+TGFβ+ cells have been recently described in chickens that have immunoregulatory properties and play a role in the pathogenesis of Marek’s Disease Virus. Methods To evaluate if CD4+CD25+TGFβ+ cells infiltrated the bursa of Fabricius (BF) following IBDV infection, and influenced the outcome of infection, birds were inoculated at either 2 days or 2 weeks of age with vaccine strain (228E), classic field strain (F52/70), or PBS (mock), and bursal cell populations were quantified by flow cytometry. Results Both 228E and F52/70 led to atrophy of the BF, a significant reduction of Bu1+-B cells, and a significant increase in CD4+ and CD8α+ T cells in the BF, but only F52/70 caused suppression of immune responses to a test antigen in younger birds, and clinical signs in older birds. Virus was cleared from the BF more rapidly in younger birds than older birds. An infiltration of CD4+CD25+T cells into the BF, and elevated expression of bursal TGFβ-1+ mRNA was observed at all time points following infection, irrespective of the strain or age of the birds, but CD4+TGFβ+cells and CD4+CD25+TGFβ+ cells only appeared in the BF at 28 dpi in younger birds. In older birds, CD4+TGFβ+ cells and CD4+CD25+TGFβ+ cells were present at earlier time points, from 7dpi following 228E infection, and from 14 and 28 dpi following F52/70 infection, respectively. Discussion Our data suggest that an earlier infiltration of CD4+TGFβ+ cells into the BF correlated with a delayed clearance of virus. However, the influx of CD4+TGFβ+ cells and CD4+CD25+TGFβ+ into the BF did not correlate with increased pathogenicity, or immunosuppression.